Phage Display-Based Nanotechnology Applications in Cancer Immunotherapy - Martina Goracci; Ymera Pignochino; Serena Marchiò (Molecules, 2020)
Phage display is a nanotechnology with limitless potential, first developed in 1985 and still awaiting to reach its peak. Awarded in 2018 with the Nobel Prize for Chemistry, the method allows the isolation of high-affinity ligands for diverse substrates, ranging from recombinant proteins to cells, organs, even whole organisms. Personalized therapeutic approaches, particularly in oncology, depend on the identification of new, unique, and functional targets that phage display, through its various declinations, can certainly provide. A fast-evolving branch in cancer research, immunotherapy is now experiencing a second youth after being overlooked for years; indeed, many reports support the concept of immunotherapy as the only non-surgical cure for cancer, at least in some settings. In this review, we describe literature reports on the application of peptide phage display to cancer immunotherapy. In particular, we discuss three main outcomes of this procedure: (i) phage display-derived peptides that mimic cancer antigens (mimotopes) and (ii) antigen-carrying phage particles, both as prophylactic and/or therapeutic vaccines, and (iii) phage display-derived peptides as small-molecule effectors of immune cell functions. Preclinical studies demonstrate the efficacy and vast potential of these nanosized tools, and their clinical application is on the way.